Integração regional: Mercosul e o direito da integração - Oliveira Junior, Erick Menezes de (2008)
The process of globalization and regional integration are directly related, which have been given greater importance from the neoliberal model of rule implemented by the end of the last century. It will demonstrate, that Brazil and Argentina the most delayed the integration process because of mutual distrust and a model of development toward the reality of inner states. Thus, only started the construction of a regional integration from 1985, when they realized the need to strengthen in the international arena. With this objective was formed Mercosur in 1991, which despite its audacious goals, establishment of a Common Market, presents a simplistic legal structure. So, will consider the main legal instruments that guided the formation of Mercosur, notably, the Treaty of Asuncion and the Protocol of Ouro Preto, and the organs that are part of that organization. It will examine how it is carried out the relationship between the domestic and international standards, noting the main theories of matter, and the positioning of Argentina and Brazil in the face of that issue. There will be specifically the reality of Mercosur, looking as if it handles the incorporation of legal rules arising from derivatives and the economic bloc by States Parties, notably by Brazil. In addition, there will be the current stage of the process of regional integration, from the analysis of the Law of Integration and the necessity of carrying out change the rules of Mercosur and the National Law of States Parties with the aim to deepen the process regional integration